PANCASILA DAN GOOD GOVERNANCE: STRATEGI MEMPERKUAT AKUNTABILITAS PUBLIK DALAM KONTEKS POLITIK IDENTITAS - Rahayu, Adinda Eka; Rizky Setyawan, Mohammad Afrizal; Al Mujahidin, Sulthonika Mahfudz Al Mujahidin; Nur Fauzi, M. Asif (Prodi PPKn Universitas Slamet Riyadi, 2024)
The narratives of identity politics emerging ahead of the 2024 Elections threaten the unity of Indonesia's pluralistic nation. This research explores how Pancasila can reinvigorate the spirit of unity in the face of this unsettling vortex of identity politics. Employing a qualitative approach, the study investigates Pancasila's role as the unifying thread of diversity in bolstering public accountability and good governance. The findings reveal that identity politics jeopardize social stability and public trust in the government. Therefore, strategic steps are needed to implement Pancasila's values, such as transparency, participation, and non-discriminatory law enforcement. Pancasila must serve as the moral foundation for clean, effective, and integrity-based governance in weaving the nation's diversity. This research recommends revitalizing the understanding of Pancasila and integrating good governance principles into government policies. It is expected to guide Indonesia towards dignified progress by uniting to face global challenges. Are you interested in learning more about how Indonesia can embody the spirit of Bhinneka Tunggal Ika amidst the swirling currents of identity politics?